Dynamics Of Social Life-Economy Of Ex-Tapol In South Blitar 1968-2000 - Masruroh, Binti; Swastika, Kayan; Sumarjono, Sumarjono; Na’im, Mohamad; Pratama, Akhmad Ryan; Jamil, Robit Nurul (JURNAL HISTORICA, 2022)
This article examines the life of Ex-Tapol in South Blitar and the survival efforts amid the new order government's discriminatory regulations against Ex-Tapol. The Study is discusses (1) what are the supervisions carried out by local governments that affect the social life – Economy of Ex-Tapol, (2) how the dynamics of the social - economic life of Ex Tapol in South Blitar 1968 - 2000. The method used in this study is a historical research method. The method used in this study is a historical research method. Use document sources, interviews, and supporting secondary sources. The results of this study are: Local government supervision of Ex-Tapol including the mandatory reporting policy, disenfranchisement of civil rights and political rights, and provision of a special code (ET) on the ID cards of ex-tapols. Many former Tapol in South Blitar worked as a farmer. The existence of a regulation that Ex-Tapol and his descendants are prohibited from having certain jobs and are prohibited from being civil servants makes Ex-Tapol in South Blitar have no other choice, but to become a farmer. The income as a farmer is uncertain, making some ex-Tapol in South Blitar increase their income by raising livestock such as cows, goats, and chickens. The interaction of Ex-Tapol with the surrounding community is partly closed because of the stigma that the Ex Tapol PKI which is an enemy of the state made some people in South Blitar choose to stay away from Ex Tapol and are reluctant to have a relationship with Ex Tapol. Keywords: Socio economic life, former political prisoner, Blitar